PERVASIVE MELT PERCOLATION REACTIONS IN ULTRA-DEPLETED REFRACTORY HARZBURGITES AT THE MID-ATLANTIC RIDGE, 15° 20′N: ODP HOLE 1274A - Seyler M.; Lorand J.-P.; Dick H.J.B.; Drouin M. (My University, 2007)
ODP Leg 209 Site 1274 mantle peridotites are highly refractory in terms of lack of residual clinopyroxene, olivine Mg# (up to 0.92) and spinel Cr# (~0.5), suggesting high degree of partial melting (>20%). Detailed studies of their microstructures show that they have extensively reacted with a pervading intergranular melt prior to cooling in the lithosphere, leading to crystallization of olivine, clinopyroxene and spinel at the expense of orthopyroxene. The least reacted harzburgites are too rich in orthopyroxene to be simple residues of low-pressure (spinel field) partial melting. Cu-rich sulfides that precipitated with the clinopyroxenes indicate that the intergranular melt was generated by no more than 12% melting of a MORB mantle or by more extensive melting of a clinopyroxene-rich lithology. Rare olivine-rich lherzolitic domains, characterized by relics of coarse clinopyroxenes intergrown with magmatic sulfides, support the second interpretation. Further, coarse and intergranular clinopyroxenes are highly depleted in REE, Zr and Ti. A two-stage partial melting/melt-rock reaction history is proposed, in which initial mantle underwent depletion and refertilization after an earlier high pressure (garnet field) melting event before upwelling and remelting beneath the present-day ridge. The ultra-depleted compositions were acquired through melt re-equilibration with residual harzburgites. © Springer-Verlag 2006.
Keywords: harzburgite